Establishing Specific Conductance-Chloride Relationships for Quaternary and Bedrock Aquifers in the Twin Cities Metropolitan Area, Minnesota, United States - John R. McDaris; Joshua M. Feinberg; Jonathan Levine; Anthony C. Runkel (Earth Science, Systems and Society)
Chloride concentrations in surface and groundwater within the Twin Cities Metropolitan Area of Minnesota are increasing and hand-sample monitoring is not sufficient to understand the scale and temporal nuance of chloride concentrations within the aquifer system. We explore the relationships between chloride concentration and specific conductance (SC) in regional aquifers as a mechanism to generate a larger quantity of data related to groundwater chloride concentrations at a higher temporal frequency. Paired measurements (N = 2,118) from 1,050 wells collected between 1972 and 2022 allow statistical relationships to be generated for several aquifer units that enable the use of SC as either a direct proxy or qualitative indicator of chloride concentration going forward. In the uppermost unconsolidated Quaternary aquifer and in the immediately underlying bedrock aquifer (Platteville Formation), correlation between chloride concentration and specific conductance imply that conductances of 1,350 and 3,800 μS/cm correspond to state chronic and acute exposure standards of 230 mg/L and 860 mg/L, respectively. SC values have increased through time in bedrock aquifers that provide the region’s largest volume of residential and industrial groundwater (the Prairie du Chien and Jordan aquifers) and interpreting these changes in detail requires consideration of the local hydrogeologic context.